Prospects for the use of ferrites with high magnetic permeability and permittivity as radio-absorbing materials - V. G. Kostishin; R. M. Vergazov; S. B. Menshova; I. M. Isaev (Российский технологический журнал)
The paper presents an overview of studies on the influence of the main parameters of ferrites on their ability to absorb electromagnetic radiation in the megahertz range (more than 10 dB). The main advantage of ferrites is a high refractive index (more than 1000) in the megahertz range due to the combination of high values of magnetic and dielectric permeability, which makes it possible to produce radio-absorbing coatings of small thickness (less than 10 mm) that effectively absorb electromagnetic radiation. Studies show that the attenuation of the power of electromagnetic radiation reflected from the surface of the ferrite is due to both interference processes and the processes of dissipation of electromagnetic energy during propagation in the ferrite. The inversely proportional relationship between the refractive index and the frequency of electromagnetic radiation in the megahertz range provides the condition for the interference minimum of the reflected radiation at a constant thickness of the ferrite coatings. A high refractive index slows down the speed of propagation of electromagnetic waves in ferrites, which enhances the processes of dissipation of their energy. The paper presents studies on the influence of the basic chemical composition of ferrites, alloying additives, microstructure parameters and technological modes on their magnetic and dielectric permeability. Studies have shown that an excess of iron oxide in excess of stoichiometry, which provides the semiconducting properties of ferrite grains, significantly increases the dielectric constant. High values of the dielectric constant of ferrites are provided by a combination of the dielectric properties of grain-boundary layers and the semiconducting properties of the grains themselves, which form the barrier capacity of grain boundaries according to the Okazaki mechanism. Alloying ferrites with oxides TiO2, Bi2O3, CaO in an amount of up to 1 wt.% allows increasing the electrical resistance and dielectric constant of grain-boundary layers, providing an increase in the dielectric constant of ferrite as a whole. It has been established that the formation of a dense coarse-grained structure provides an increase in both the magnetic permeability and permittivity.